Pengaruh Independensi, Kompetensi dan Pengalaman Audit terhadap Kemampuan Pendeteksian Kecurangan dengan Skeptisisme Profesional sebagai Variabel Moderasi - Natasya, Nindy; Mhd Karya Satya Azhar; Ruswan Nurmadi (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2024)
This research aims to determine the effect of independent, competence and audit experience on fraud detection capabilities with professional skepticism as a moderating variable at Public Accounting Firms in Medan City. This research uses a saturated sampling method (census), namely a sampling method when the entire population is sampled. This saturated sampling method was used because the entire population in this reseacrh was 108 auditors. Of the 108 auditors at the Public Accounting Firm in Medan City, 64 samples were obtained which could be used as data in the research. The data used in this research is primary data, namely in the form of a questionnaire using questions stated on a Likert scale of 1 to 5. The results of this research indicate that the independence variable has no effect on the ability to detect fraud. Meanwhile, the competency and audit experience variables have a significant effect on the ability to detect fraud. . Professional skepticism is unable to moderate the influence of independence, competence and audit experience on the ability to detect conditions. Professional skepticism is unable to moderate the influence of independence, competence and audit experience on the ability to detect conditions.